A REVIEW OF EFFECTIVENESS AND SAFETY OF SELECTED BIOLOGICS IN THE TREATMENT OF RHEUMATOID ARTHRITIS - Kariuki, Stephen Mwaura; E.K, Kemoi; Musyoki, Stanslaus Kiilu (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
Background: Rheumatoid arthritis (RA) is an autoimmune disease that causes disability to patients in the long run. The bone and cartilage degradation are driven by pro-inflammatory cytokines like tumour necrosis factor alpha (TNF-α) and interleukin-6 (IL-6) among others. The traditional treatment for RA is disease modifying anti-rheumatic drugs (DMARDs) despite the serious adverse effects. In the last past few years biologics have been added to DMARDs or replaced them altogether in the treatment of RA. There is however, growing concern on the effectiveness and safety of these biologics. Aim: This article reviewed the use of Rituximab, Adalimumab, and Golimumab, as well as dnaJP1 peptide and Folate-targeted immunotherapy data to assess their effectiveness and safety in the treatment of RA. Methods: Data from clinical trials and other animal model experiments published in peerreviewed journal articles were reviewed to determine the effectiveness and safely levels of these biologics as used in the treatment of rheumatoid arthritis. Results: We found that combination therapy of biologics and DMARDs has proven effective in the treatment of RA especially where the latter have failed to reduce disease activity in patients. Rituximab has been found effective where monotherapy treatment with DMARDs and anti-TNFs have failed. Conclusion: All biologics are generally effective and safe for use in the treatment of RA with minimal side effects being reported.